DAT SPECT may have diagnostic value in prodromal SCA2 patients with parkinsonism. (November 2017) - Miyaue, Noriyuki; Tada, Satoshi; Ando, Rina; Iwaki, Hirotaka; Yabe, Hayato; Nishikawa, Noriko; Nagai, Masahiro; Takashima, Hiroshi; Nomoto, Masahiro
Abstract: Introduction: Although spinocerebellar ataxia type 2 (SCA2) is classified as hereditary spinocerebellar degeneration, some patients present with parkinsonism before developing cerebellar ataxia. Methods: 123 I-metaiodobenzyl guanidine ( 123 I-MIBG) myocardial scintigraphy and/or dopamine transporter single photon emission computed tomography (DAT SPECT) using 123 I-ioflupane ( 123 I-FP-CIT) were performed for the six patients from three SCA2 families. Results: 123 I-MIBG myocardial scintigraphy showed reduced cardiac uptake in four of five patients and an association with Lewy body disease was suggested. DAT SPECT showed decreased uptake in the striatum in all four patients who were scanned, including one patient without parkinsonism. When patterns of uptake were compared to those with Parkinson's disease, most of the patients had minimal reduction of uptake in the putamen. Conclusion: DAT SPECT is expected to be useful in differentiating SCA2 from Parkinson's disease, making an early diagnosis, and allowing early therapeutic intervention. Highlights: Levodopa responsive parkinsonism is one of symptoms in SCA2 cases. Parkinsonism can be one of preclinical symptoms in SCA2 cases. DAT SPECT can lead to implementation of the early treatment in SCA2 cases.